DEVELOPMENT OF SMOKED FISH BUSINESS IN PENATARSEWU VILLAGE AS AN EFFORT TO EMPOWER THE COMMUNITY ECONOMY - Balqis, Diana; Mursyidah, Lailul (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: The research aims to analyze the development of smoked fish businesses as a strategy for strengthening local economic capacity and independence. Method: A qualitative descriptive case study was conducted using in-depth interviews, participant observation, and documentation involving business owners, village officials, and community leaders. Results: The findings indicate that smoked fish businesses significantly contribute to increasing income, fostering independence in production and distribution, and generating local employment opportunities. Innovations such as modern smoking technology and packaging training have enhanced product competitiveness and extended shelf life, while digital marketing initiatives have begun to expand market reach, although access to training and support remains uneven among business owners. Novelty: This research highlights the integration of local potential with technological innovation and policy support as a sustainable model of community empowerment, demonstrating that the synergy of communities, academics, and private actors can transform traditional businesses into resilient local economic drivers rooted in local wisdom.